Tin, Bismuth, and Tin–Bismuth Alloy Electrodeposition from Chlorometalate Salts in Deep Eutectic Solvents. Issue 3 (13th April 2017) - Vieira, Luciana; Burt, Jennifer; Richardson, Peter W.; Schloffer, Daniel; Fuchs, David; Moser, Alwin; Bartlett, Philip N.; Reid, Gillian; Gollas, Bernhard
Abstract: The electrodeposition of tin, bismuth, and tin–bismuth alloys from Sn II and Bi III chlorometalate salts in the choline chloride/ethylene glycol (1:2 molar ratio) deep eutectic solvent was studied on glassy carbon and gold by cyclic voltammetry, rotating disc voltammetry, and chronoamperometry. The Sn II ‐containing electrolyte showed one voltammetric redox process corresponding to Sn II /Sn 0 . The diffusion coefficient of [SnCl3 ] −, detected as the dominating species by Raman spectroscopy, was determined from Levich and Cottrell analyses. The Bi III ‐containing electrolyte showed two voltammetric reduction processes, both attributed to Bi III /Bi 0 . Dimensionless current/time transients revealed that the electrodeposition of both Sn and Bi on glassy carbon proceeded by 3D‐progressive nucleation at a low overpotential and changed to instantaneous at higher overpotentials. The nucleation rate of Bi on glassy carbon was considerably smaller than that of Sn. Elemental Sn and Bi were electrodeposited on Au‐coated glass slides from their respective salt solutions, as were Sn–Bi alloys from a 2:1 Sn II /Bi III solution. The biphasic Sn–Bi alloys changed from a Bi‐rich composition to a Sn‐rich composition by making the deposition potential more negative. Abstract : More complex : For the first time, chlorometalate salts are used as precursors in the electrodeposition of alloys from deep eutectic solvents. The reduction of the complexes and the nucleation of Sn and Bi are studied and the biphasic alloys are characterized.